2015
DOI: 10.1111/febs.13592
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori CagA protein induces factors involved in the epithelial to mesenchymal transition (EMT) in infected gastric epithelial cells in an EPIYA‐ phosphorylation‐dependent manner

Abstract: As a result of Helicobacter pylori adhesion to gastric epithelial cells, the bacterial effector cytotoxin-associated gene A (CagA) is translocated intracellularly, and after hierarchical tyrosine phosphorylation on multiple EPIYA motifs, de-regulates cellular polarity and contributes to induction of an elongation and scattering phenotype that resembles the epithelial to mesenchymal transition (EMT). Stromelysin-1/matrix metalloproteinase-3 (MMP-3) has been reported to induce a sequence of molecular alterations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 69 publications
0
39
0
1
Order By: Relevance
“…Accumulating evidence has indicated that EMT is a critical process not only in normal development but also in oncogenesis in recent years [25][26][27]. Cancer cells were endowed with increased motility and invasiveness during this process.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has indicated that EMT is a critical process not only in normal development but also in oncogenesis in recent years [25][26][27]. Cancer cells were endowed with increased motility and invasiveness during this process.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-3 was shown to promote EMT and was suggested to be a natural tumor promoting factor [80,81]. MMP-3 expression in response to H. pylori was suggested to depend on the presence of phosphorylated CagA EPIYA motifs in gastric adenocarcinoma cell lines and is regulated alike the EMT markers ZEB1 (zinc finger E-box-binding homeobox 1), vimentin, snail, and CD44 [82]; However, this dependency on CagA was not observed in mouse infection models [75]. It is conceivable, that the different regulation in vivo might be attributed to IL-1β dependent secretion of MMP-3 [79].…”
Section: Deregulation Of Extracellular Host Proteases By H Pylorimentioning
confidence: 99%
“…Sougleri et al [42] observed the morphological and polarity changes characteristic of EMT in response to Caga. Using mutant gastric epithelial cells expressing variant forms of Caga with differing numbers of EPIYA (Glu-Pro-Ile-Tyr-Ala)-binding sites, they noted that phosphorylation of those sites mediates the interaction of Caga with SHP-2 noted above, leading to an elongated cell structure resembling that of the EMT and known as the ‘hummingbird’ phenotype.…”
Section: Introductionmentioning
confidence: 99%